2009
DOI: 10.1177/0022034509352958
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol Gum and Maternal Transmission of Mutans Streptococci

Abstract: An important caries prevention strategy for children includes measures to interfere with transmission of mutans streptococci (MS). This study confirmed the effectiveness of maternal early exposure to xylitol chewing gum on mother-child transmission of MS. After screening, 107 pregnant women with high salivary MS were randomized into two groups: xylitol gum (Xylitol; n = 56) and no gum (Control; n = 51) groups. Maternal chewing started at the sixth month of pregnancy and terminated 13 months later in the Xylito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 18 publications
(24 reference statements)
3
53
1
8
Order By: Relevance
“…A recent study found that a maternal xylitol consumption by gum provided better preventive outcomes on salivary MS levels among there children, as compared with fluoride varnish treatments 16 . Another study concluded that this intervention should be targeted to women with high levels of MS counts 17 . The maternal use of xylitol reduces also caries incidence and restorative treatment needs in children that were expected to be high caries risk to the average level 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a maternal xylitol consumption by gum provided better preventive outcomes on salivary MS levels among there children, as compared with fluoride varnish treatments 16 . Another study concluded that this intervention should be targeted to women with high levels of MS counts 17 . The maternal use of xylitol reduces also caries incidence and restorative treatment needs in children that were expected to be high caries risk to the average level 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol chewing gum, a type of sugar-free chewing gum, is a well-known and effective strategy for preventing caries (Isokangas et al 1988;Machiulskiene et al 2001;Burt 2006), and acts primarily by inhibiting Streptococcus mutans plaque Nakai et al 2010;Seki et al 2011;Shinga-Ishihara et al 2012). Moreover, the use of xylitol chewing gum as an adjunct to tooth brushing is beneficial for oral hygiene including plaque control, based on a systematic review of the literature (Keukenmeester et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle hamilelere uygulanan çürük önle-yici programlarda ksilitollü sakızlar önerilebilir. 25 Süt dişlenme sürecinde sorbitol, ksilitol ve bunların kombinasyonlarını içeren sakızların çürük önleyici etkisi olduğu kanıtlanmıştır. 26 Ksilitol ve sorbitollü sakızların etkinliğinin karşılaştırılması sonucunda, sorbitollü grupta SM düzeyi daha yüksek bulunmuştur.…”
Section: Ksilitolunclassified